f ' (1) = (3x-4)(5x-6) thanks in advance!
Follow Math Help Forum on Facebook and Google+
Originally Posted by calcconfused f ' (1) = (3x-4)(5x-6) thanks in advance! You will need to use the product rule. f'(x) = fg'+f'g =(3x-4)(5)+ (3)(5x-6) Then plug in 1 for your x values.
Originally Posted by mollymcf2009 You will need to use the product rule. f'(x) = fg'+f'g =(3x-4)(5)+ (3)(5x-6) Then plug in 1 for your x values. thats what i thought it was but apparently the answer is 30(1) - 38 = -8 i dk how that is the answer
nevermind i figured it out THANKS
View Tag Cloud